Personal Hygiene Yang Buruk Meningkatkan Kejadian Pediculosis Capitis Pada Santri Santriwati Di Pondok Pesantren - Fitra Pringgayuda; Gita Anggelia Putri; Andri Yulianto (Jurnal Keperawatan Muhammadiyah, 2021)
Objective:  This study aims to determine the relationship between hygiene and the incidence of pediculosis capitis among female students in Islamic boarding schools. Methods: This article used analytic observational with crossectional approach. The samples used 89 female students in  Islamic boarding schools  Miftahul Falah Banyu Mas Pringsewu Lampung.  Data collection using a questionnaire instrument that has been validated and reliabilitis. statistical test using the chi square test.Results: :The result shows respondent characteristics based on age is most respondents aged 12 years (23.8%) and based on class levels most were in 7th grade. Most respondents did not do good personal hygiene (65%). Most of the respondents have experienced pediculosis capitis (67.5%). There is a relationship between personal hygiene with the incidence of pediculosis capitis in Miftahul Falah Islamic Boarding School Banyumas Pringsewu Lampung in 2020 with p value = 0,000; OR= 19,167 (5,881-62,471)Conclusion:  Poor personal hygiene can increase the incidence of pediculosis capitis in students in Miftahul Falah Islamic Boarding School